1996
DOI: 10.1111/j.1399-6576.1996.tb04383.x
|View full text |Cite
|
Sign up to set email alerts
|

Does epidural sufentanil provide effective analgesia per‐and postoperatively for abdominal aortic surgery?

Abstract: To assess the efficacy of epidural sufentanil in providing per- and postoperative analgesia, 40 patients undergoing elective abdominal aortic surgery received either 50 mu g sufentanil in 10 ml normal saline solution (n = 20, ES group) or 10 ml normal saline (n = 20, control group) via a thoracic epidural catheter. The study solution was given (double-blind and at random) after the patients had been anaesthetized with i.v. midazolam, sufentanil and vecuronium. Anaesthesia was maintained with 60% nitrous oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…[6] Fentanyl, with its rapid onset, has for long been widely used in cardiac anesthesia and analgesia, since it does not cause cardiovascular depression. [7] However, there is a limited number of studies comparing these two analgesic substances in terms of preventing the effects of postoperative pain.…”
mentioning
confidence: 99%
“…[6] Fentanyl, with its rapid onset, has for long been widely used in cardiac anesthesia and analgesia, since it does not cause cardiovascular depression. [7] However, there is a limited number of studies comparing these two analgesic substances in terms of preventing the effects of postoperative pain.…”
mentioning
confidence: 99%
“…1 Its analgesic efficacy at low-doses (2.5-10 µg) combined to a local anesthetic is well documented in obstetrics where it improves analgesia during labour and intraoperative Cesarean delivery. [9][10][11][12][13] In abdominal surgery, sufentanil is usually administered epidurally or intravenously 14,15 and the clinical experience in non-vascular major abdominal surgery with ITS is still limited. A recent study in major abdominal surgery showed that a large dose of ITS (150 µg) was able to blunt the intraoperative stress response and produced effective analgesia, but was associated with prolonged mechanical ventilation.…”
mentioning
confidence: 99%